2022
DOI: 10.3390/ani12131690
|View full text |Cite
|
Sign up to set email alerts
|

Disenfranchised Guilt—Pet Owners’ Burden

Abstract: Guilt refers to an unpleasant emotional state associated with one’s behaviors, thoughts, or intentions, and it is based on the possibility that one may be in the wrong or that others may have this perception. Parental guilt is one common subtype and is often associated with work–family conflict (WFC). WFC and related guilt have been found to be associated with depression and anxiety. Through an online anonymous survey, the current study was designed to explore dog owners’ guilt surrounding their dogs. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 121 publications
1
7
0
Order By: Relevance
“…Our findings, similar to earlier research, suggest that the most bereaved pet owners maintain ongoing, meaningful ties with their deceased pet (Carmack, 1985; Cowles, 1985; Kogan, Bussolari, et al, 2022; Packman et al, 2011). In addition to the reported use of CB practices, we found that participants reported that all of the CB expressions they chose were more comforting than distressing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings, similar to earlier research, suggest that the most bereaved pet owners maintain ongoing, meaningful ties with their deceased pet (Carmack, 1985; Cowles, 1985; Kogan, Bussolari, et al, 2022; Packman et al, 2011). In addition to the reported use of CB practices, we found that participants reported that all of the CB expressions they chose were more comforting than distressing.…”
Section: Discussionsupporting
confidence: 90%
“…An increasing number of people view their pets as family members (Kogan, Bussolari, et al, 2022; Kogan, Wallace, et al, 2022; Rowan & Kartal, 2018) with studies consistently reporting that the depth of attachment and connection humans feel toward their pets parallels bonds between people (Archer, 1997; Behler, 2020; Carmack, 1985; Cowling et al, 2020; DeGroot, 1984; Field et al, 2009; Messam & Hart, 2019). Bowlby's attachment theory, although originally referring to the relationship between a child and a primary caregiver (Bowlby, 1973), has been frequently applied to better understand the human-animal attachment relationship (Jenkins et al, 2014; Peacock et al, 2012; Teo & Thomas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Guilt refers to an unpleasant emotional state associated with one’s behaviors, thoughts or intentions and is based on the possibility that one may have wronged others, regardless of whether any actual physical, psychological, or emotional harm has taken place [ 138 140 ]. A recent study by Kogan et al [ 141 ] found that people with pets report guilt scores similar to those reported in studies assessing parents and their human children, with female pet owners reporting higher levels of guilt than male pet owners. Pet-related guilt is often unrecognized, yet, similar to parental guilt [ 142 144 ] it may lead to feelings of anxiety depression and poor psychological health [ 141 ].…”
Section: Discussionmentioning
confidence: 53%
“…A recent study by Kogan et al [ 141 ] found that people with pets report guilt scores similar to those reported in studies assessing parents and their human children, with female pet owners reporting higher levels of guilt than male pet owners. Pet-related guilt is often unrecognized, yet, similar to parental guilt [ 142 144 ] it may lead to feelings of anxiety depression and poor psychological health [ 141 ]. The guilt items endorsed the most frequently in the current study included ‘I feel guilty when I do not have the energy to fully engage with my pet because of my cancer’ (agree or strongly agree: 71%), ‘I feel bad that I am unable to spend more time with my pet because of my cancer’ (agree or strongly agree: 65%), and ‘I feel bad when I have to put my own needs ahead of my pet because of my cancer’ (64%).…”
Section: Discussionmentioning
confidence: 53%
“…not able to walk or feed the dog), was correlated with poorer owner well-being in all aspects assessed. The sense of failure to provide optimal care for the dog per se is an obvious explanation for poorer well-being, as it may contribute to guilt and bad feelings about the relationship with the dog 27 , 50 . It is also possible that factors such as repeated failure reflect a disturbed owner routine which counteracts the benefits to human well-being suggested by having a dog-related routine 4 , 5 , 25 , 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%